Non-local dilaton coupling to dark matter: cosmic acceleration and pressure backreaction - Amendola, Luca; Gasperini, Maurizio; Ungarelli, Carlo (Arxiv, 2007)
A model of non-local dilaton interactions, motivated by string duality symmetries, is applied to a scenario of "coupled quintessence" in which the dilaton dark energy is non-locally coupled to the dark-matter sources. It is shown that the non-local effects tend to generate a backreaction which -- for strong enough coupling -- can automatically compensate the acceleration due to the negative pressure of the dilaton potential, thus asymptotically restoring the standard (dust-dominated) decelerated regime. This result is illustrated by analytical computations and numerical examples.
Gesehen am 15.11.2017